The role of meteorological tsunamis on beach erosion in the buenos aires coast: some numerical experiments. Issue 3 (3rd July 2018) - Alonso, Guadalupe; Dragani, Walter; Pérez, Iael
ABSTRACT: Meteorological tsunamis (meteotsunamis) are very similar to ordinary tsunamis but are produced by atmospheric processes. In this work, some numerical experiments are performed using XBeach numerical model investigate the role of moderate meteorological tsunamis on a sandy beach. The model was forced using tide, a moderate storm surge event, wave height data series and a meteorological tsunami event recorded in the Buenos Aires coast, Argentina. Several numerical experiments were carried out considering different time lags between the peak level of the meteotsunami event and the highest sea level (storm surge and tide). In these experiments, the volumes of moved sand were quite similar, although different erosion patterns on the beach were appreciated. Numerical experiments presented in this work constitute the first indication that the occurrence of regular meteotsunamis during moderate storm conditions could change the erosion pattern on sandy beaches in the coast of Buenos Aires.